2013
DOI: 10.1093/jrr/rrt040
|View full text |Cite
|
Sign up to set email alerts
|

Data-driven Markov models and their application in the evaluation of adverse events in radiotherapy

Abstract: Decision-making processes in medicine rely increasingly on modelling and simulation techniques; they are especially useful when combining evidence from multiple sources. Markov models are frequently used to synthesize the available evidence for such simulation studies, by describing disease and treatment progress, as well as associated factors such as the treatment's effects on a patient's life and the costs to society. When the same decision problem is investigated by multiple stakeholders, differing modellin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The robustness of data‐driven models relates to how often observations (data or variables) can be related to an outcome according to certain relationships (equations). As such, data‐driven NTCP models may be able to identify models that perform better than mechanistic counterparts, given sufficient data, or that depart significantly from standard therapeutic strategies, such as charged particle therapy …”
Section: Radiogenomic Modeling: Mechanistic Data‐driven and Machinementioning
confidence: 99%
“…The robustness of data‐driven models relates to how often observations (data or variables) can be related to an outcome according to certain relationships (equations). As such, data‐driven NTCP models may be able to identify models that perform better than mechanistic counterparts, given sufficient data, or that depart significantly from standard therapeutic strategies, such as charged particle therapy …”
Section: Radiogenomic Modeling: Mechanistic Data‐driven and Machinementioning
confidence: 99%
“…Clearly, any state-discrete model belongs to this class, though it might be possible, that models with hybrid state-space are output-discrete if the continuous parts of the state-space are not considered as model-output. The best examples for this feature are found in classic microsimulation models or, to be precise, Markov models for health technology assessment (HTA, see [Abler et al, 2013]), wherein discrete health-states are observed, while (potentially) continuous patient parameters like age or blood values may have an influence on the transition probabilities between the health-states, but are not focus of interest. Anyway, in case of state-/output-discrete microscopic models there is a bijective mapping of Γ/Γ onto a subset of N d .…”
Section: Classification With Respect To State-spacementioning
confidence: 99%
“…In the current thesis only statecontinuous microscopic models without contacts were discussed, namely the groundwater pollution random-walk model 5.1 and the agent-based GEPOC model 6.1. Examples for output-/state-discrete microscopic models without interaction are the mentioned HTA focussed Markov models [Abler et al, 2013].…”
Section: Classification With Respect To Interaction Levelmentioning
confidence: 99%
“…[16][17][18] They provide support for evaluating uncertainties in decision making by approximating patient transitions through a set of "health states", each of which corresponds to a clinical event. 19 While using Markov chains has been useful for chronic conditions such as COPD, directly using EHR data in Markov models presents certain challenges. In particular, Markov chains assume a one-step time-invariant transition.…”
Section: Background and Significancementioning
confidence: 99%